Non‐isothermal self‐sustained one pot dissolution of metal values from manganese nodules using NH3OHCl as a novel reductant in sulfuric acid medium. Issue 6 (29th October 2012) - Hariprasad, D.; Mohapatra, M.; Anand, S.
Abstract: Background: In view of depleting grades of land based ores, deep sea manganese nodules have become an important future resource of Cu, Ni, Co and Mn. A number of studies have been reported for the dissolution of metal values but till now no process has been commercialized and efforts are continuing to develop a process using an environmentally acceptable reductant. In the present study a novel reductant NH3 OHCl has been used to develop a process . Results: Dissolution studies were carried out by varying a number of experimental parameters. The optimum conditions established for >98% extraction of Cu(II), Ni(II), Co(II) and Mn(II) are: pulp density 20% (wt/v), time 20 min, reductant 8 g per 20 g of nodule and H2 SO4 5% (v/v). The heat of mixing the reagents and fast instantaneous reactions automatically raised the slurry temperature and within a period of 20 min, it was possible to dissolve quantitatively the above said metal values. The leach solution was purified following (i) Fe(II) oxidation to Fe(III) by KMnO4 solution, (ii) iron removal by pH adjustment and (iii) precipitation of bulk sulfide by Na2 S. A simplified flow‐sheet has been presented . Conclusions: The deep sea nodules were leached under non‐isothermal conditions using a novel reductant, i.e. hydroxyl ammonium chloride in sulfuric acid medium. No external heat was needed for quantitative dissolution of Mn, Cu, Ni and Co values. A simple process has been presented for the treatment of Mn nodules .